Diagnostic challenge in chondromyxoid fibroma clinically mimicking neuroma - Masłowska, Aleksandra Izabela; Sołek, Julia; Jagodzińska-Mucha, Paulina; Braun, Marcin; Romańska, Hanna (Contemporary Oncology/Współczesna Onkologia, 2024)
Chondromyxoid fibromas (CMF) are uncommon benign bone tumours, known for their moderate risk of local recurrence, that may manifest through various symptoms such as pain, swelling, tenderness, or be asymptomatic. Diagnosing CMF is challenging and requires a comprehensive, multidisciplinary diagnostic approach because the tumour frequently resembles numerous other bone lesions. This report describes a case of a 66-year-old female patient with a tumour in her right fibula. The initial diagnosis of a neuroma of the right tibial nerve was based on a magnetic resonance imaging scan. The lesion was surgically removed. Preliminarily subsequent histopathological evaluation identified the mass as a parosteal osteosarcoma. However, due to the uncharacteristic presentation of the tumour, further investigation was carried out. Using immunohistochemical and genetic analyses focused on the expression of MDM-2 and RB-1, along with an examination for alterations in the GNAS gene, the mass has been finally and conclusively identified as a chondromyxoid fibroma. This case demonstrates the ambiguity of the CMF presentation, the accurate diagnosis of which may frequently rely on additional diagnostic measures, including histopathology and targeted genetic tests. Furthermore, this report illustrates an atypical diagnostic journey, from an initial neuroma through a low-grade osteosarcoma, to a final benign chondromyxoid fibroma.